The practice of entepreneurship - Meredith, Geoffrey G.; Nelson, Robert E.; Neck, Philip A. (Lagos, Nigeria : University of Lagos Press, 1991)
The work is in three parts. Part I deals with the internal or personal characteristics and behavioural traits of enterpreneurs. Part II refers specifically to financial aspects of entrepreneurship in which business success is most commonly reflected. Part III is about the external aspects of entrepreneurship, such as dealing with people able to help enterpreneurs.
aia 26/8/16 ; rua 09/11/19
Loans
Keywords: Entrepreneurship